VEGETATIVE VIGOR OF MAIZE CROP OBTAINED THROUGH VEGETATION INDEXES IN ORBITAL AND AERIAL SENSORS IMAGES - Santana, L.S.; Ferraz, G.A e S.; Santos, L.M.; Maciel, D.A.; Barata, R.A.P.; Reynaldo, Ã‰. F.; Rossi, G. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Currently, images from unmanned aerial vehicles (UAVs) are being used due to their high spatial and temporal resolution. Studies comparing different mobile data acquisition platforms, such as satellites, are important due to the limited spatial and temporal resolution of some satellites as well of the presence of clouds in such images. The objective of this study was to compare the vegetation indices (VIs) generated from images obtained by orbital (satellite) and sub-orbital (unmanned aerial vehicles - UAV) platforms. The experiment was conducted in a maize-growing area in Paraná, Brazil. Landsat 8 and UAV images of the study area were collected. Four VIs were applied: NDVI, VIgreen, ExG and VEG. The NDVI was selected as the control and compared with the other VIs. There was a good correlation (0.79) between the NDVI and the VEG for the UAV images. For the Landsat images, the highest correlation found was between the NDVI and the VIgreen derived from UAV images, which was 0.89. It is concluded that the images obtained by UAVs generated better indices, mainly in the dry season.